2011
DOI: 10.1021/ef101740b
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Factors Responsible for the Rheology Change of a Brazilian Crude Oil under Magnetic Fields

Abstract: Recently, some works showed that magnetic fields may reduce the paraffin crystallization and the viscosity of some types of oil. This Article shows the main results obtained in an attempt to determine some factors responsible for the oil interaction with magnetic fields, which caused the rheological properties change in crude oil samples. Under the influence of a magnetic field (1.3 T in 1 min exposure), one of the six brazilian crude oil samples studied (sample 1) showed 39% reduction on its viscosity and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…They found out that under a 0.3 T magnetic field, the crystallization was lower than that without the effect of a magnetic field. However, they also found that rheological changes in crude oil due to magnetic fields exposure is strongly dependent on the crude constitution (Gonçalves et al 2011).…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…They found out that under a 0.3 T magnetic field, the crystallization was lower than that without the effect of a magnetic field. However, they also found that rheological changes in crude oil due to magnetic fields exposure is strongly dependent on the crude constitution (Gonçalves et al 2011).…”
Section: Magnetic Fieldmentioning
confidence: 99%
“…They claimed their method gave a linear response over the range 8 to at least 100 mg g À1 Cl. An interesting study was undertaken by Goncalves et al 204 who used EPR (electron paramagnetic resonance), XRF and NMR to investigate the recent claim that magnetic fields can reduce the crystallisation of paraffin and the viscosity of some types of oil. They found that one of six Brazilian crude oil samples showed a reduction in viscosity when exposed to a large magnetic field but the others did not.…”
Section: Geologicalmentioning
confidence: 99%
“…Due to the risk of pipeline blockage caused by wax deposition, the flow assurance of waxy oil in a pipeline has drawn much attention . Related studies aiming at hindering or mitigating the severe wax deposition process included heat application, pipe coating, electrical or magnetic treatment, , chemical agent, , etc. Among chemical agents, pour point depressant (PPD) treated an effective material with less dosage and low cost tackling wax deposition problem was widely used .…”
Section: Introductionmentioning
confidence: 99%